2020
DOI: 10.2174/1874312902014010022
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Hepatic Micro-Hypodensities as a Presenting Sign in Systemic Lupus Erythematosus- A Case Report

Abstract: Systemic Lupus Erythematosus (SLE) is a chronic multisystemic inflammatory disorder that can present with a wide array of signs and symptoms. Hepatic involvement is commonly limited to a subclinical biochemical transaminitis while clinically significant liver disease is rare. A case of a 22-year-old female who presented with abdominal pain, fevers, arthralgia, and several hepatic hypodense lesions with normal liver function tests is reported in this study. She failed to improve with antibiotics and infectious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 14 publications
(11 reference statements)
0
14
0
Order By: Relevance
“…In retrospective studies, liver function abnormalities have been found in a significant proportion of SLE patients, and the diagnosis of liver disease often occurs after the diagnosis of SLE 1,2 . Hepatic vasculitis, although rare, has been reported in a small number of SLE cases 4,5,9 . However, there is conflicting data on the incidence of hepatic vasculitis in SLE due to variations among different studies 1–10 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In retrospective studies, liver function abnormalities have been found in a significant proportion of SLE patients, and the diagnosis of liver disease often occurs after the diagnosis of SLE 1,2 . Hepatic vasculitis, although rare, has been reported in a small number of SLE cases 4,5,9 . However, there is conflicting data on the incidence of hepatic vasculitis in SLE due to variations among different studies 1–10 .…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the absence of infectious features, the presence of autoimmune thrombocytopenia, and the patient's response to corticosteroid therapy supported the diagnosis of hepatic vasculitis. The management of hepatic vasculitis in SLE involves immunosuppressive therapy to control disease activity and prevent further vascular damage 4,5,9 . High‐dose corticosteroids are commonly used as the initial treatment, with the addition of other immunosuppressive agents if necessary 4,5,9 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations